2018
DOI: 10.1016/j.celrep.2018.02.103
|View full text |Cite
|
Sign up to set email alerts
|

Cas4 Facilitates PAM-Compatible Spacer Selection during CRISPR Adaptation

Abstract: SummaryCRISPR-Cas systems adapt their immunological memory against their invaders by integrating short DNA fragments into clustered regularly interspaced short palindromic repeat (CRISPR) loci. While Cas1 and Cas2 make up the core machinery of the CRISPR integration process, various class I and II CRISPR-Cas systems encode Cas4 proteins for which the role is unknown. Here, we introduced the CRISPR adaptation genes cas1, cas2, and cas4 from the type I-D CRISPR-Cas system of Synechocystis sp. 6803 into Escherich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(144 citation statements)
references
References 48 publications
6
130
2
1
Order By: Relevance
“…The new casposons encode several nucleases that have not been previously observed in family 1, including OLD family nucleases (in NitDev-C1 and NitNF5-C1), NERD domain-containing nuclease related to Holliday junction resolvases (NitNF5-C1) and HNH nuclease (NitNF5-C1). Most notably, NitNF5-C2 encodes two homologues of the Cas4 nuclease, which is involved in the adaptation process in many CRISPR-Cas systems (Hudaiberdiev et al, 2017;Kieper et al, 2018;Lee et al, 2018;Shiimori et al, 2018), and might participate in casposon integration, which is mechanistically closely similar to CRISPR spacer integration (Béguin et al, 2016;Krupovic et al, 2017). Both Cas4 copies display closest sequence similarity to Cas4 homologues from different Clostridia.…”
Section: Five Major Classes Of Thaumarchaeal Mgementioning
confidence: 99%
“…The new casposons encode several nucleases that have not been previously observed in family 1, including OLD family nucleases (in NitDev-C1 and NitNF5-C1), NERD domain-containing nuclease related to Holliday junction resolvases (NitNF5-C1) and HNH nuclease (NitNF5-C1). Most notably, NitNF5-C2 encodes two homologues of the Cas4 nuclease, which is involved in the adaptation process in many CRISPR-Cas systems (Hudaiberdiev et al, 2017;Kieper et al, 2018;Lee et al, 2018;Shiimori et al, 2018), and might participate in casposon integration, which is mechanistically closely similar to CRISPR spacer integration (Béguin et al, 2016;Krupovic et al, 2017). Both Cas4 copies display closest sequence similarity to Cas4 homologues from different Clostridia.…”
Section: Five Major Classes Of Thaumarchaeal Mgementioning
confidence: 99%
“…In most of the prokaryotes, specificity of CRISPR adaptation machinery drives the uptake of phage-origin prespacers that are bordered by a PAM sequence (McGinn and Marraffini, 2019). Though the removal of Cas4 in S. islandicus (type I-A), Synechocystis sp.6803 (type I-D) and P. furiosus (type I-G) didn't hamper spacer uptake completely, deficiency of this nuclease led to plummeted PAM preference (Kieper et al, 2018;Shiimori et al, 2018;Zhang et al, 2019). Likewise, mutations in metal coordinating residues (K102A and D87A) of RecB domain of Cas4-Cas1 fusion from G. sulfurreducens (type I-U) led to skewed PAM specificity (Almendros et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of such DNA fragments is infinitesimal in the RecBCD products, hinting at the involvement of an additional processing step to generate befitting substrates. Recent studies in Sulfolobus solfataricus (type I-A), Sulfolobus islandicus (type I-A), Bacillus halodurans (type I-C), Synechocystis sp.6803 (type I-D), Pyrococcus furiosus (type I-G) and Geobacter sulfurreducens (type I-U) (Almendros et al, 2019;Kieper et al, 2018;Lee et al, 2018;Liu et al, 2017;Rollie et al, 2018;Shiimori et al, 2018;Zhang et al, 2019) highlighted the indispensable role of Cas4 nuclease in PAM selection and prespacer processing. The occurrence of Cas4 is predominantly limited to type I CRISPR-Cas system with the exception of subtypes I-E and I-F .…”
Section: Introductionmentioning
confidence: 99%
“…Primers for sub-cloning are listed in Table S1. The ihf-α and ihf-β genes were PCR amplified from E. coli (BL21) genomic DNA using the indicated primers in Table S1 and subsequently cloned into Berkeley MacroLab ligation-independent cloning (LIC) vectors using either LIC into 13K-HR and 13S-A vectors respectively, as described previously (Kieper et al, 2018). The ihf-α gene was cloned as an N-terminal His6 tag.…”
Section: Protein Preparationmentioning
confidence: 99%
“…However, in vivo only correctly oriented spacers with respect to PAM sequence will result in functional crRNAs for target recognition (Jackson et al, 2017;McGinn and Marraffini, 2019). Recent in vivo and in vitro studies using type I-A, I-B, I-C and I-D revealed the critical role of Cas4 in PS DNA maturation and the fidelity of spacer integration (Hou and Zhang, 2018;Kieper et al, 2018;Lee et al, 2018;Rollie et al, 2018;Shiimori et al, 2018). However, it is unknown how Cas4-deficient systems such as E. coli type I-E determine the correct orientation of new spacers.…”
Section: Introductionmentioning
confidence: 99%